A predicted model for postoperative seizure outcomes after the surgical resection of supratentorial cavernous malformations. Issue 26 (June 2016) - Wang, Chun; Yu, Xiaobo; Shrestha, Sudeep; Qian, Cong; Wang, Lin; Chen, Gao
Abstract : Abstract: To explore a predicted model for postoperative seizure outcomes after the surgical resection of supratentorial cavernous malformations. This study was a retrospective review of consecutive patients with cerebral supratentorial cavernous malformations presenting with seizures. All patients underwent surgical resection of CCMs. Univariate and multivariate analyses were performed to determine the predictive value of the preoperative seizure frequency, seizure type, seizure duration, lesion location, lesion size, and the presence of residual hemosiderin. A total of 43 patients met the inclusion criteria. After a mean follow-up period of 40.95 months, 34 patients who were free from postoperative seizures were classified into Engel class I, and the remaining 9 patients were classified into Engel classes II–IV. A univariate analysis showed that the seizure frequency (χ 2 = 13.440, P = 0.004) and seizure duration (χ 2 = 5.145, P = 0.023) prior to surgery were associated with a worse postoperative seizure prognosis. Other covariates including age at onset, gender, a history of the medications taken, smoking status, family history, lesion characteristics, and the role of hemosiderin were not related to seizure outcomes. Logistic regression results demonstrated that the preoperative seizure frequency was an effective predictor ( P = 0.004). The receiver operating characteristic curve indicated that area under the curve for the preoperative seizure frequency test was 0.833 (95% confidence interval 0.709–0.957, P = 0.002). The preoperative seizure frequency was a prognostic factor for postoperative seizure outcomes after surgical resection of supratentorial cavernous malformations. To obtain a favorable prognosis for CCM patients with preoperative seizures, early intervention might be a better choice.